Comparing conventional and modified Seldinger techniques using a micro-insertion kit for PICC placement in neonates: a retrospective cohort study - van Rens, Matheus F. P. T.; Hugill, Kevin; van der Lee, Robin; Francia, Airene L. V.; van Loon, Fredericus H. J.; Bayoumi, Mohammad A. A. (Frontiers in Pediatrics, 2024)
Objective This study aims to assess the comparative effectiveness of a conventional splitting needle or a peelable cannula vs. the modified Seldinger technique (MST) by utilizing a dedicated micro-insertion kit across various clinically significant metrics, including insertion success, complications, and catheter-related infections. Methods We conducted a retrospective observational cohort study using an anonymized data set spanning 3 years (2017–2019) in a large tertiary-level neonatal intensive care unit in Qatar. Results A total of 1,445 peripherally inserted central catheter (PICC) insertion procedures were included in the analysis, of which 1,285 (89%) were successful. The primary indication for insertion was mainly determined by the planned therapy duration, with the saphenous vein being the most frequently selected blood vessel. The patients exposed to MST were generally younger (7 ± 15 days vs. 11 ± 26 days), but exhibited similar mean weights and gestational ages. Although not statistically significant, the MST demonstrated slightly higher overall and first-attempt insertion success rates compared to conventional methods (91 vs. 88%). However, patients undergoing conventional insertion techniques experienced a greater incidence of catheter-related complications (p < 0.001). There were 39 cases of catheter-related bloodstream infections (CLABSI) in the conventional group (3.45/1,000 catheter days) and eight cases in the MST group (1.06/1,000 catheter days), indicating a statistically significant difference (p < 0.001). Throughout the study period, there was a noticeable shift toward the utilization of the MST kit for PICC insertions. Conclusion The study underscores the viability of MST facilitated by an all-in-one micro kit for neonatal PICC insertion. Utilized by adept and trained inserters, this approach is associated with improved first-attempt success rates, decreased catheter-related complications, and fewer incidences of CLABSI. However, while these findings are promising, it is imperative to recognize potential confounding factors. Therefore, additional prospective multicenter studies are recommended to substantiate these results and ascertain the comprehensive benefits of employing the all-in-one kit.